Bone Mesenchymal Stem Cells with Growth Factors Successfully Treat Nonunions and Delayed Unions. Issue 2 (July 2015) - Desai, Pingal; Hasan, Saad Mumtaz; Zambrana, Lester; Hegde, Vishal; Saleh, Anas; Cohn, Matthew R.; Lane, Joseph M.
Background: While the gold standard of treatment of nonunion is open autologous bone grafting, studies have shown that injecting bone marrow aspirate concentrates (BMAC) is effective in treating tibial nonunions with fracture gaps less than 5 mm. Questions/Purposes: We aim to demonstrate that combining BMAC with osteoinductive agents can effectively treat delayed or nonunion regardless of fracture gap size, nonunion site, or osteoinductive agent used. Methods: In this non-randomized retrospective-prospective cohort study, 49 patients with tibial nonunion met the inclusion criteria and underwent BMAC injection with demineralized bone matrix (DBM) and/or recombinant human bone morphogenic protein-2 (rhBMP-2). Radiologic healing of the fracture was the primary outcome. Patients were followed until radiographic union was achieved or another procedure was performed. Radiographic healing was defined as bridging of three out of four cortices on anteroposterior and lateral films. Results: There was no difference in the healing rate ( p = 0.81) between patients with fracture gaps less than and greater than 5 mm. On multivariate analysis, the use of rhBMP-2 was associated with a lower healing rate compared to DBM ( p = 0.036). Patients who underwent early intervention (within 6 months of fixation) had higher union rates ( p = 0.04). Conclusion: This study shows that percutaneous BMAC injection combined with either DBM and/or rhBMP-2 is a safe and effective treatment for delayed or nonunion regardless of the fracture gap size or fracture site. DBM may be superior to rhBMP-2 in this procedure.